P 59 Mimicking phase-amplitude coupling: The influence of burst frequency in EEG-TMS plasticity induction. (May 2022) - Baur, D.; Zrenner, C.; Ziemann, U.
Abstract : The induction of TMS plasticity-like effects in the human motor cortex has been shown to be dependent on the phase of the local sensorimotor µ-oscillation at the time of stimulation. Targeting the negative peak, which is the high excitability state, results in facilitatory plasticity (Zrenner et al., 2018; Baur et al., 2020), yet the underlying physiological processes remain to be further elucidated. Phase-amplitude coupling is an ubiquitous phenomenon in the human cortex and is assumed to play an crucial role in learning and synaptic plasticity induction (Canolty and Knight, 2010). This process is defined by the coupling of high-gamma power to a specific phase of a lower frequency oscillation. We hypothesize that mimicking this process by application of TMS bursts in a physiological high-gamma frequency range at the negative peak of the µ-oscillation will lead to more efficacious plasticity induction compared to other frequencies. We address this question in healthy subjects using a real-time-EEG-triggered TMS set-up whereby the µ-oscillation is extracted by a C3-Laplacian montage. The left hand knob is stimulated, and right hand MEPs are recorded before and for 60 min after a 200 quadruplet bursts TMS intervention. Five intervention conditions are tested in separate sessions in randomized order: quadruplet bursts on the µ-oscillation negative peak at a frequency of (1) 60 Hz, (2) 100 Hz, (3) 200 Hz or (4) 666 Hz, and (5) 200 Hz uncoupled to the ongoing µ-oscillation. This study will have substantial implication for understanding the neurophysiology underlying TMS plasticity induction and for further development of individual EEG-triggered stimulation protocols, enabling a more effective therapeutic TMS application in neuropsychiatric conditions. The study is work in progress. Findings will be provided on the conference.